2023
DOI: 10.1002/alz.12956
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell counts in cerebrospinal fluid predict cognitive function in aging and neurodegenerative disease

Abstract: IntroductionImmune dysfunction is important in aging and neurodegeneration; lacking clinically available tools limits research translation. We tested associations of cerebral spinal fluid (CSF) monocyte‐to‐lymphocyte ratio (MLR)—innate immune activation surrogate—with cognition in an aging and dementia cohort, hypothesizing that elevated MLR is associated with poorer executive functioning.MethodsCSF MLR was calculated in well‐characterized, genotyped participants enrolled in studies of aging and dementia at Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…There is growing recognition of the role of in ammation and immune dysregulation in neurodegeneration, including the development of a pro-in ammatory milieu in the central nervous system. 45 Genes implicated in both monogenic neurodegenerative disease as well as risk genes are related to microglia and immune pathways, such as APOE, TREM2, and TBK1, and many of which were also identi ed in our microglial transcriptomic and proteomic data. Like the observations seen in this family, clonal expansion of CD4 and CD8 positive T-cells have been described in amyotrophic lateral sclerosis type four and frontotemporal dementia patients, further supporting a link between immune dysregulation and disease.…”
Section: Discussionmentioning
confidence: 78%
“…There is growing recognition of the role of in ammation and immune dysregulation in neurodegeneration, including the development of a pro-in ammatory milieu in the central nervous system. 45 Genes implicated in both monogenic neurodegenerative disease as well as risk genes are related to microglia and immune pathways, such as APOE, TREM2, and TBK1, and many of which were also identi ed in our microglial transcriptomic and proteomic data. Like the observations seen in this family, clonal expansion of CD4 and CD8 positive T-cells have been described in amyotrophic lateral sclerosis type four and frontotemporal dementia patients, further supporting a link between immune dysregulation and disease.…”
Section: Discussionmentioning
confidence: 78%
“…This finding highlights the value of CSF inflammation indicators in identifying connections between innate immune dysfunction and neurodegenerative processes. 21 This immune dysfunction was previously thought to be restricted to the CNS, but accumulating data indicate pivotal contributions of the peripheral immune system as well.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the higher incidence of nosocomial pneumonia might contribute to the poor prognosis. Another study involving 199 patients found a negative correlation between MLR in cerebrospinal fluid and executive function in elderly patients with dementia, suggesting that inflammatory markers could predict neurodegenerative changes [ 32 ]. In our study, we divided patients into three subgroups based on MLR levels using a tertile method.…”
Section: Discussionmentioning
confidence: 99%